A Study of Adverse Childhood Experiences, Coping Strategies, Work Stress, and Self-Care in the Child Welfare Profession. Issue 4 (8th August 2017) - Lee, Kyuho; Pang, Yuk C.; Lee, Jo Ann L.; Melby, Janet N.
ABSTRACT: This mixed-method study examines child welfare professionals' adverse childhood experiences (ACE) and coping strategies they use to mitigate work stress. Survey data are from 104 child welfare services professionals in a Midwestern state. Participants reported high stress levels and frequent unhealthy coping strategies. Their ACE scores were higher than those of the general population. Quantitative analyses showed that the relativity of ACE to their career choice and unhealthy coping strategies also predicted their work stress. Qualitative analysis revealed challenges these workers face in self-care when dealing with work stress. Implications for child welfare staff, supervisors, and educators are suggested.